DESAIN PEMBELAJARAN UNTUK MISKONSEPSI PECAHAN PADA SISWA SEKOLAH DASAR: SEBUAH SYSTEMATIC LITERATURE REVIEW - Sunandar; Kholid, Idham; Chandra, Muhamad Raj; Parid, Miptah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Fraction misconceptions represent a persistent epistemological obstacle among elementary school students globally and contribute to difficulties in learning mathematics at subsequent educational levels; however, comprehensive syntheses regarding their typologies, causes, and interventions remain limited. This study aims to identify the types of fraction misconceptions, analyze their contributing factors, and synthesize effective pedagogical interventions to remediate these misconceptions among elementary school students. The method employed was a systematic literature review following the PRISMA protocol, encompassing 48 indexed empirical articles published between 2011 and 2025, retrieved from the Scopus, Web of Science, ERIC, and Google Scholar databases. The findings revealed three primary typologies of fraction misconceptions: fundamental concept misconceptions, comparison and ordering misconceptions, and operational misconceptions, with multifactorial causes encompassing epistemological, didactical, and students' personal cognitive factors. Pedagogical interventions proven effective include the use of manipulative media, the Realistic Mathematics Education (RME) approach, cognitive conflict strategies, and the integration of adaptive technology. This study concludes that remediating fraction misconceptions necessitates a holistic approach that simultaneously integrates various intervention strategies, with recommendations for teachers to conduct early diagnosis and for future researchers to develop technology-based diagnostic assessment instruments and longitudinal studies to examine the sustainability of intervention effects.